Japanese Journal of Ophthalmology The Official International Journal of the Japanese Ophthalmological Society - Sawa, Mitsuru; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer.)
The Japanese Journal of Ophthalmology (JJO) was inaugurated in 1957 as a quarterly journal published in English by the Ophthalmology Department of the University of Tokyo, with the aim of disseminating the achievements of Japanese ophthalmologists worldwide. JJO remains the only Japanese ophthalmology journal published in English. In 1997, the Japanese Ophthalmological Society assumed the responsibility for publishing the Japanese Journal of Ophthalmology as its official English-language publication. Currently the journal is published bimonthly and accepts papers from authors worldwide. JJO has become an international interdisciplinary forum for the publication of basic science and clinical research papers. We encourage authors to submit original papers in all fields of ophthalmology.
Keywords: Ophthalmology; Ophthalmology